Biocontrol potential of bacteria isolated from Carpobrotus spp. as seed treatments against Fusarium pathogens of maize - Kritzinger, Quenton (University of Pretoria, 2024)
Dissertation (MSc (Plant Science))--University of Pretoria, 2019.